Risk Factors and Chemical Composition of Urinary Stones in the Azorean Population (São Miguel Island - Portugal): A Preliminary Study - Silva Linhares, Diana Paula (2018)
Introduction: Urinary stone disease is one of the most common disorders of the urinary tract. However, the main risk factors and chemical composition of urinary stones in the population of the Azores are unknown. The objective of this study was to define the most important factors associated with the formation of urinary calculi, investigating eating habits, family history and chemical composition of the calculi in the population of the Azores. Methods: The data were collected from 46 patients of the Hospital do Divino Espirito Santo and 48 healthy volunteers. A questionnaire was recorded on the medical and family history of the participants and on their life habits. The chemical composition of the calculi was evaluated by ICP-MS. Results: It was observed that the study group has a higher prevalence of diabetes and cases of urinary calculi in the family compared to the reference group. A positive correlation was found between calcium in the stones and the contents of sodium, magnesium, zinc, molybdenum and strontium. Conclusion: This study reveals that family history, diabetes and water consumption play an important role in the development of urinary calculi in the population of the Azores. The chemical content of the stones should also be considered since these data could help the medical community to understand the causes of urinary stone formation and adapt the medication and preventive measures to the patient and to the type of kidney stone produced.